How to show the working for equation (-3)²+(-2)².
Answers
Answered by
1
Answer:
Hello please mark my answer as brianliest
Step-by-step explanation:
As when know when bases are same powers are added in addition and subtracted when in division
But here it is not that type of cases
so what we will do is..
we will multiply - 3 two times as its power is 2 and multiply - 2 two times as its power is also 2 , we get ;
-3*-3 = 9
-2*-2 = 4
9 raise power 2 + 4 raise power 2 =
9+4 = 13 raise power two
OR
(-3)² + (-2)²
= -3²+-2²
= -3²-2²
= -5²
Hope it helps...
Thanks....
Please mark me as brainliest ....
Similar questions